Pemanfaatan Campuran Myrmecodia Pendans dan Piper Crocatum Sebagai Green Corrosion Inhibitor pada Inhibitor Kimia Jenis Koktail untuk Proteksi Korosi Baja API 5L Grade B dalam Larutan NaCl 3,5% - Agus Budiono; Yudha Pratesa; Rani Kusumawardani; Johny Wahyuadi Soedarsono (MBI, 2025)
Method to prevent the corrosion during pipeline hydrotest using seawater is generally by the addition of inorganic inhibitor containing corrosion inhibitor agent, oxygen scavenger and biocide, so that require to find out the alternative eco-friendly materials with better performance. The main objective of this study is to investigate the efficiency of the use of mixture of extract of Myrmecodia pendans and Piper crocatum as an alternative of eco-friendly inhibitor for reducing the use of inorganic inhibitors for corrosion protection of steel material API 5L Grade B in 3.5% NaCl. The corrosion inhibition ability of natural ingredient extraction are investigated by using tafel polarization test and EIS and verified by weight loss test. The content of the active compounds in natural ingredient extraction along with adsorption compound on metal surfaces and inhibition mechanism are investigated by EIS, FTIR and adsorption isotherm model. In the mixed green inhibitor concentration of 2 ml Myrmecodia pendans and 1 ml Piper crocatum is resulted in approximately 73.66% inhibitor efficiency while concentration of 1 ml chemical cocktail and 2 ml green inhibitor are significantly reduce the corrosion rate from 0.42 mm/year to be 0.03 mm/year with approximately 93.15% inhibitor efficiency. The green inhibitor affected the cathodic as well as the anodic polarization curves which were known as mixed corrosion inhibitor type. The adsorption of compounds contained in the Myrmecodia pendans and Piper crocatum on a metal surface are occur spontaneously follows the Langmuir adsorption isotherm.